ANALISIS KEPUASAN KERJA DAN LINGKUNGAN KERJA TERHADAP LOYALITAS KARYAWAN Z & J BAKERY KUNINGAN - Nahdiah, Fina Ainun; Syafrudin, Oding; Akbar, Ilham (Universitas Kuningan, 2024)
This study aimed to examine the effect of job satisfaction and work environment on employee loyalty. The sample in this study were employees of Z&J Bakery Kuningan with a sample of 82 and using saturated sampling techniques. This research conducts testing using the Statistical Program for Social Sciences (SPSS) version 23. The method used is descriptive method to know as widely as possible about the object of research at a certain time. What becomes this research is job satisfaction and work environment which are independent variables (free variables) and dependent variables (related variables) which are employee loyalty. This research instrument is a physical questionnaire containing statements and distributed to respondents. The results of this study concluded that (1) job satisfaction has no effect on employee loyalty. (2) work environment has a positive and significant effect on employee loyalty. (3) job satisfaction and work environment simultaneously have a positive and significant effect on employee loyalty.